Journal of pharmaceutical policy and practice (BioMed Central, 2013)
"Journal of Pharmaceutical Policy and Practice (formerly known as Southern Med Review) is an open access, peer-reviewed journal. It provides a platform for researchers to disseminate empirical research findings, with the aim that people everywhere have access to the medicines they need and use them rationally. Journal of Pharmaceutical Policy and Practice encompasses all aspects of pharmacy whether clinical, social, administrative or economic, and provides a platform to researchers, academics and practitioners from around the world to share new evidence, concerns and perspectives."